Studying sediment transport dynamics by using the Smart sphere - Alhusban, ZaidZaid; Valyrakis, Manousos (جامعة الوادي - university of el oued, 2020)
A new method is introduced by using high precision accelerometer and gyroscope micro-electromechanical sensors (MEMS), which can record Lagrangian observations of sediments and shed light into the dynamics of sediment transport processes at above threshold conditions. The sensor can be used under a range of well-controlled flow conditions and can record measurements at high frequency (200 Hz), which can be used at the field. The smart sphere performance was evaluated by comparing its rotation and acceleration readings from the sensors to the video recordings of both top and underwater high-speed camera for a range of flow rates and sphere densities. Furthermore, an initial attempt to compare the smart-sphere’s velocity is achieved, by transforming the particle’s velocity from the Lagrangian frame of reference, obtained from the inertial sensor, to its velocity at the Eularian frame, obtained from the top camera.
Article
Keywords: Lagrangian, high frequency, velocity, micro-electomechanical sensors